ANALISIS HASIL SASARAN KINERJA PEGAWAI (SKP) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SERANG - Herni Herawati; Lusi Emilia Wulandari; Devi Noviana; Syamsul Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to evaluate employee performance targets at the Population and Civil Registration Service (Disdukcapil) of Serang City, with a focus on its impact on improving public services. This study was conducted using a case study approach to explore how the established performance targets play a role in achieving organizational goals and the quality of service to the community. Through an analysis of performance policies, implementation processes, and evaluation of employee work results, this study hopes to provide recommendations for improving the quality of public services through more effective employee performance management.